Case report: Familial foveal retinoschisis caused by CRB1 gene mutation in a family with recessive inheritance - Liu, Shu; Ren, Yue; Wang, Di; Xiao, Dan; Li, Zhuang; Xu, Dan; Sun, Yan; Wang, Zhuoshi; Pang, Jijing (Frontiers in Medicine, 2023)
X-linked retinoschisis is more common in male children and rare in females. Clinically, male patients mainly present with early onset visual impairment or vision loss, and retinal retinoschisis due to division of the inner retina. We report a long-term observation of a female patient with familial foveal retinoschisis (FFR) caused by CRB1 gene with complex heterozygotic mutation. The initial symptoms of the female patient reported in this study were very similar to some early manifestations of X-linked retinoschisis (XLRS) caused by RS1 mutations involving macular fovea. However, as time going on, the splitting height at retinal fovea of FFR gradually decreased, and the splitting extent at retinal fovea of FFR gradually decreased.